The Development of Electronic Modules Based on Problem Based Learning Integrating Disaster Mitigation in Environmental Change Material to Increase Critical Thinking Skills of Students - Sinta Kusuma Dewi; Hadi Suwono; Hendra Susanto (BIOEDUKASI, 2023)
An e-module is a learning media designed to assist students in discovering and solving problems independently and can be used practically and flexibly. The purpose of this paper is to produce a PBL-based integrated disaster mitigation e-module on environmental change material that is valid, practical and effective. The e-module development used the development model by (Lee & Owens, 2004). E-modules were validated by material experts, learning media experts, biology education experts and practitioners. Furthermore, the e-modules were tested on students in individual, small group and field trials. In the field trial, the e-module was applied in biology learning. Based on the N-Gain test score between pretest and posttest, it is known that the experimental class is in the high category and the control class is in the medium-high category. The results prove that the e-module developed is valid, practical and effective, so it can be used in learning activities that can improve students' critical thinking skills.